Земельное обеспечение православных приходов Северной Таврии в дореформенный период - Маковский, В.В.; Сухарев, М.В. (Культура народов Причерноморья, 2013)
В статье рассматривается вопрос об особенностях обеспечения земельными наделами православных причтов в материковых уездах Таврической губернии в дореформенный период (до 1861 г.). Особое внимание уделяется законодательному сопровождению данного процесса, взаимоотношениям таврического приходского духовенства с местными властями, регулированию прав собственности на церковную землю. У статті розглядається питання про особливості забезпечення земельними наділами православних причтів у материкових повітах Таврійської губернії в дореформений період (до 1861 р.). Особлива увага приділяється законодавчому супроводженню даного процесу, взаємовідносинам таврійського парафіяльного духовенства з місцевою владою, регулюванню прав власності на церковну землю. In article the question of features of providing by allotments of orthodox parishes in continental districts of the Taurian province during the prereform period (till 1861) is considered. The special attention is paid to legislative maintenance of this process, relationship of Taurian parishional clergy with local authorities, to regulation of the property rights to the church land. The authors investigating subject of this article are specified. Data on providing with land resources of orthodox parishes of Dneprovsky and Melitopol districts of the Taurian province in the 30th of the XIX century, about an average proportion of the land on the temple are provided in Northern Tavriya in 1852. The issue of lack of allotments is touched at Taurian city temples, attempt of its decision in the district city of Alyoshky is considered. Authors on the basis of archival materials analyze attempts of misappropriation of church lands. In article the comparative analysis of size of parishional plots and the sizes of noble latifundiyas is provided in Northern Tavriya on the example of possession of the favourite of the Russian empress Ekaterina II of prince Grigory Potyomkin. The problem of allocation of the land plot for construction of the parishional house in Melitopol, a role of the Taurian governor in its decision is considered. The question of an involvement of Taurian priests in system of the market relations, about existence of preferences for them is at the same time investigated from local authorities. In article dependence between the right of peasants to a laying of the new orthodox temple and obligatory allocation of an allotment from their possession for future parish on the example of Rubanovk's state settlement of the Dneprovsky district is shown.